Study of the impact of educational behavioral interventions on fatigue in mothers in the postpartum period in the groups of face-to-face and electronic training - Zahra Gholami; Soheila Mohammadirizi; Parvin Bahadoran (Wolters Kluwer Medknow Publications, 2017)
Background: Maternal fatigue in the postpartum period include factors that affect the quality of life and health of both the mother and newborn. This study aimed to investigate two educational approaches regarding mother's fatigue in the postpartum period. Materials and Methods: This experimental study was performed among 110 pregnant mothers during their postpartum care using random sampling. The participants were divided in three groups, namely, face-to-face, e-learning, and control groups. Interventions included individual meetings between the researcher and mothers in the face-to-face group and giving educational compact disc to the e-learning department to improve maternal fatigue. Personal information and fertility data was obtained (before training); the maternal fatigue questionnaire Fatigue Severity Scale (FSS) was completed before and after any type of (face-to-face, e-learning, and control) education. Obtained data were analyzed using one-way analysis of variance (ANOVA) and repeated-measures ANOVA. Results: Results showed that both face-to-face and e-learning methods had similar maternal fatigue scores. The average change on the maternal fatigue score in the second treatment was (p = 0.02) and the third treatment was (p < 0.001)among three groups that was indicative of significant statistical differences. Similarly, there was no statistically significant difference in the average maternal fatigue score between the two groups before the intervention and in the second and third groups after the intervention. Therefore, over time, the training was unaffected. Conclusions: The findings of this study indicate that both face-to-face and e-learning methods are effective to reduce maternal postpartum fatigue.